The changing link between labor cost and price inflation in the United States - Elena Bobeica; Matteo Ciccarelli; Isabel Vansteenkiste (European Central Bank (ECB), 2021)
The link between US labor cost and price inflation has weakened notably over the past three decades. In this paper we document this decline and analyse potential contributing factors. We consider four important trends that have shaped the US economy of late: (i) improved anchoring of inflation expectations; (ii) the changing constellation of shocks hitting the economy; (iii) increased trade integration and (iv) rising firm market power. We find that the improved anchoring of inflation expectations has played a particularly relevant role but also that the latter two trends offer promising avenues to understand the decline in pass-through from labor cost to price inflation. Our results also bring supportive evidence to the view taken by the FED in the context of its monetary policy strategy review that a robust job market can be sustained without causing an outbreak of inflation.
Keywords: C32; E24; E31; 330; Inflation; pass-through; labor costs; structural VAR; United States